PERAN KEPUASAN KERJA DALAM MEMEDIASI PENGARUH SERVANT LEADERSHIP DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI - Ade Mardiana; Djatmiko Noviantoro; Sari Sakarina (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This study examines the mediating role of job satisfaction in the relationship between servant leadership, organizational culture, and employee performance in a provincial education office in South Sumatra. This research applies a quantitative approach using a survey method involving civil servants as respondents. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings indicate that servant leadership and organizational culture significantly influence job satisfaction. Furthermore, servant leadership, organizational culture, and job satisfaction have a positive and significant impact on employee performance. Job satisfaction partially mediates the relationship between servant leadership and employee performance as well as between organizational culture and employee performance. These findings emphasize the importance of leadership practices oriented toward service and the strengthening of organizational culture to enhance employee performance in public sector institutions.